Modulus stabilization in a non-flat warped braneworld scenario - Indrani Banerjee (European Physical Journal C: Particles and Fields, 2017)
Abstract The stability of the modular field in a warped brane world scenario has been a subject of interest for a long time. Goldberger and Wise (GW) proposed a mechanism to achieve this by invoking a massive scalar field in the bulk space-time neglecting the back-reaction. In this work, we examine the possibility of stabilizing the modulus without bringing about any external scalar field. We show that instead of flat 3-branes as considered in Randall–Sundrum (RS) warped braneworld model, if one considers a more generalized version of warped geometry with de Sitter 3-brane, then the brane vacuum energy automatically leads to a modulus potential with a metastable minimum. Our result further reveals that in this scenario the gauge hierarchy problem can also be resolved for an appropriate choice of the brane’s cosmological constant.